2001
DOI: 10.1074/jbc.m105178200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-Kinase Is Necessary but Not Sufficient for Thrombopoietin-induced Proliferation in Engineered Mpl-bearing Cell Lines as Well as in Primary Megakaryocytic Progenitors

Abstract: Mature megakaryocytes are large, polyploid bone marrow cells that give rise to circulating platelets (1). Thrombopoietin (TPO) 1 has been characterized as the primary hematopoietic cytokine regulating normal megakaryocyte (MK) development. The receptor for TPO is encoded by the c-mpl proto-oncogene, a member of the hematopoietic growth factor receptor family, which in altered form causes a myeloproliferative syndrome in mice (2). In addition to its effects on MK development, TPO has been found to play a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 60 publications
0
76
0
1
Order By: Relevance
“…23,71,121,204 However, it should not been overlooked that many cytokines activate PI3K/Akt signaling which therefore would seem to play an important role in erythropoiesis, myelopoiesis and thrombocytopoiesis. [244][245][246][247] Clearly, these results have been obtained in vitro and they might not reflect what happens in vivo. In addition, also in this field the findings are conflicting, as exemplified by a recent paper which suggests that EPO downregulates PI3K/Akt axis during erythropoiesis through upregulation of phosphatidylinositol 4-phosphatase II, 248 whereas other reports have suggested a key role for PI3K/Akt in EPO-mediated erythroid differentiation.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 98%
“…23,71,121,204 However, it should not been overlooked that many cytokines activate PI3K/Akt signaling which therefore would seem to play an important role in erythropoiesis, myelopoiesis and thrombocytopoiesis. [244][245][246][247] Clearly, these results have been obtained in vitro and they might not reflect what happens in vivo. In addition, also in this field the findings are conflicting, as exemplified by a recent paper which suggests that EPO downregulates PI3K/Akt axis during erythropoiesis through upregulation of phosphatidylinositol 4-phosphatase II, 248 whereas other reports have suggested a key role for PI3K/Akt in EPO-mediated erythroid differentiation.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 98%
“…Both kinases and phosphatases play imperative roles in signaling through surface receptors by regulating the state of cellular phosphorylation. In addition to the Jak/ STAT signaling pathway, TPO has been shown to stimulate Ras/Raf/MAPK, and PI3K/Akt, affecting cell survival, growth, and differentiation Rojnuckarin et al, 1999;Geddis et al, 2001). Studies have now shown that the Src family of tyrosine kinases (SFKs) are activated and are involved in TPO signaling networks (Santini et al, 2002;Lannutti et al, 2003;Lannutti and Drachman, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…MKs cell differentiation and proliferation are regulated by a number of cytokines; however, thrombopoietin (TPO) is the primary regulator of MK maturation including cellular enlargement and nuclear polyploidy. TPO binding to its cognate receptor, Mpl, results in the activation of a variety of signaling events including the Janus kinase (JAK)/signal transducer and activator of transcription (STAT), ras/raf/MAP kinase, and PI-3 kinase/Akt pathways Rojnuckarin et al, 1999;Geddis et al, 2001). Although Mpl lacks intrinsic kinase activity, dimerization of the receptor results in a rapid increase in tyrosine phosphorylation, in large part due to the transphosphorylation and activation of JAK2 Drachman et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, by itself, PI3K is critical for cellular proliferation and survival (31) and may thus provide essential signals for the growth of cells containing truncated receptors. Akt, a downstream effector of PI3K, is phosphorylated in response to TPO in BaF3/T69 cells, suggesting that the PI3K pathway can be activated by the truncated receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has shown that PI3K is essential for cellular proliferation in BaF3/Mpl and primary MK (31). As TPO-induced Akt activation is much weaker in BaF3/T69 cells than in cells with full-length Mpl, its physiological relevance needed to be determined.…”
Section: Pi3k Is Activated In Response To Tpo In Baf3/t69 Cells Andmentioning
confidence: 99%